pDNA-tachyplesin treatment stimulates the immune system and increases the probability of apoptosis in MC4-L2 tumor cells - Fatemeh Mahmoudi-Filabadi; Abbas Doosti (Amino Acids)
Abstract Breast cancer is the most common cancer among women worldwide, and marine creatures are the most abundant reservoir of anticancer medicines. Tachyplesin peptides have shown antibacterial capabilities, but their potential to inhibit cancer growth and trigger cancer cell death has not been investigated. A synthetic tachyplesin nucleotide sequence was generated and inserted into the pcDNA3.1( +) Mammalian Expression Vector. PCR analysis and enzyme digesting procedures were used to evaluate the vectors' accuracy. The transfection efficiency of MCF-7 and MCF10-A cells was 57% and 65%, respectively. The proliferation of MCF-7 cancer cells was markedly suppressed. Administration of plasmid DNA (pDNA) combined with tachyplesin to mice with tumors did not cause any discernible morbidity or mortality throughout treatment. The final body weight curves revealed a significant reduction in weight among mice treated with pDNA/tachyplesin and tachyplesin at a dose of 100 µg/ml (18.4 ± 0.24 gr, P < 0.05; 11.4 ± 0.24 gr P < 0.01) compared to the control group treated with PBS (22 ± 0.31 gr). Animals treated with pDNA/tachyplesin and tachyplesin exhibited a higher percentage of CD4 + Foxp3 + Tregs, CD8 + Foxp3 + Tregs, and CD4 + and CD8 + T cell populations expressing CTLA-4 in their lymph nodes and spleen compared to the PBS group. The groups that received pDNA/tachyplesin exhibited a substantial upregulation in the expression levels of caspase-3, caspase-8, BAX, PI3K, STAT3, and JAK genes. The results offer new possibilities for treating cancer by targeting malignancies using pDNA/tachyplesin and activating the mTOR and NFκB signaling pathways.